Evaluation of oxidative stress markers in hospitalized patients with moderate and severe COVID-19 - Zendelovska Dragica; Atanasovska Emilija; Petrushevska Marija; Spasovska Katerina; Stevanovikj Milena; Demiri Ilir; Labachevski Nikola (Sciendo, 2021)
Background. Clinical evidence suggests increased oxidative stress in COVID-19 patients and this worsened redox status could potentially contribute to the progression of the disease.